Cash transfers, migration, and gender norms - Hidrobo, Melissa; Mueller, Valerie; Roy, Shalini (Agricultural and Applied Economics Association, 2022)
Although migration remains crucial for economic development, financial constraints may limit individual ability to migrate. A recent literature demonstrates that social protection programs encourage migration; however, how norms shape the migration decision of women and men are rarely considered. Analysis of 2209 panel households (2014–2016) in Mali suggests that men predominantly move for employment, whereas women move to rural areas for marriage and urban areas for employment. We then test, in the context of a large-scale randomized controlled trial, how a cash transfer (CT) program in Mali affects the migration patterns of men and women. We find the probability of rural–rural migration among men in beneficiary households increases by 0.9 percentage points (an effect size of 100%), whereas the probability of rural–urban migration among women decreases by 0.2 percentage points (an effect size of 50%). We find no impacts on average women's rural–rural migration or men's rural–urban migration. However, women in less poor beneficiary households are more likely to engage in rural–rural migration as a result of the CT, whereas women in poorer beneficiary households realize no immediate impact. Our findings indicate that the provision of cash potentially fosters investment in profitable endeavors outside of subsistence agriculture for men but may also affect the marital migration of women.